Implementasi IoT dalam Otomasi Pengontrolan Kondisi Lingkungan dan Pemberian Pakan: Efeknya Terhadap Parameter Efisiensi Peternakan - Patria Adhistian; Miranti Mayangsari (Teknik Informatika Universitas Pamulang, 2021)
Nowday 35% of Indonesians buy poultry products every week. However, 95% of Indonesia farms are small open houses often built from bamboo using manual feeding and watering systems. The problem related to the manual feeding and watering system is the high mortality rate of poultry, which is an average of 8%. The use of IoT (Internet of Things) in agriculture and livestock is increasingly popular. This research implemented IoT on a poultry farm to automatically control environmental conditions based on sensor readings and measure feed level and water consumption. It also monitored chicken weight via a digital scale. This study also measured the farm efficiency parameters before and after IoT implementation, namely FCR, IP, and mortality rates. The results showed that the performance of IoT in poultry farms could increase efficiency. After IoT implementation, the FCR value decreased from 1.46 to 1.38, which led to an increase in the FE value to 72%. The IP score increased to 391.1. The mortality rate of chickens decreased from 3.67% to 2.35%. Also, the average weight of chickens at harvest is 1460gr. the mortality rate of chickens decreased from 3.67% to 2.35%. Also, the average weight of chickens at harvest is 1460gr.